Analisis Kandungan Metabolit Sekunder Dari Genus Dipterocarpaceae Dengan Metode Fitokimia - Herru, Yoan De Nanda; Diova Ritonga , Anggrena; Yelmiza, Yelmiza; Malas Sari, Yuni; Rokim, Muhamad (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2025)
Plants belonging to the Dipterocarpaceae family are widely distributed across various regions of Indonesia, particularly in Riau Province, which is known for its high biodiversity. This family is primarily valued for its high-quality timber, which is extensively utilized in various industries. However, beyond its economic value as a construction material, these plants also have the potential to be a source of bioactive compounds, making it essential to further investigate their secondary metabolite content. This study aims to identify and analyze the types of secondary metabolites present in five species belonging to the Dipterocarpaceae family, namely Shorea acuminata, Shorea sumatrana, Shorea belanoides, Shorea singkawang, and Shorea pinanga. To determine the presence of these bioactive compounds, this research employs the phytochemical screening method, which is a fundamental technique in the chemical analysis of plants. The results of this study indicate that all tested samples from the five species showed positive results for the presence of several major groups of secondary metabolites, namely triterpenoids, steroids, phenolics, and flavonoids. The presence of these compounds suggests that plants within the Dipterocarpaceae family have significant potential for broader applications, particularly in the pharmaceutical, cosmetic, and health industries. Compounds such as phenolics and flavonoids are well known for their antioxidant, anti-inflammatory, and antimicrobial properties, which can play a crucial role in the development of natural medicines and active ingredients for health-related products